Strong Asymmetry of Interhemispheric Ice Volume During MIS 11, MIS 9, and MIS 7 Drives Heterogeneity of Interglacial Precipitation Intensity Over Asia. Issue 18 (21st September 2022) - Cheng, Liangqing; Wu, Yubin; Song, Yougui; Yang, Linhai; Miao, Xiaodong; Sun, Huanyu; Qiang, Xiaoke; Chang, Hong; Long, Hao; Dong, Zhibao
Abstract: Gaining insight into the characteristics of past interglacials enhances our understanding of the current warm period and improves predictions of future climate. In this study, we analyze precipitation records of the past 900 ka and find that precipitation intensity during interglacials varied across Asia, especially between interglacials that occurred before and after the mid‐Brunhes transition. To clarify the mechanism of precipitation intensity variation during interglacials, we present a high‐resolution eolian record documenting the past 900 ka, which is from the thickest loess core (202.49 m) drilled in Ili Basin, Central Asia and conduct modeling with Community Earth System Model 1.2.2. We propose that sorting coefficient of Ili loess is a sensitive proxy for wind intensity, and it indirectly reflects Northern Hemisphere ice volume. Supported by numerical modeling experiments, we suggest that strong asymmetry of interhemispheric ice volume during marine isotope stages 11, 9, and 7 drives heterogeneity of interglacial precipitation intensity over Asia. Plain Language Summary: Interglacials after 430 ka (ka mean millennium) exhibit lower global ice volumes, higher global CO2 concentrations, and higher temperatures in the Southern Hemisphere than interglacials before 430 ka. This transition has become known as the mid‐Brunhes transition (MBT). However, interglacial precipitation intensities reconstructed in different regions over Asia show conflicting patterns before and after MBT. The uplift of Tibetan Plateau and changes in global ice volume fail to account for documented spatial variations of precipitation intensities during interglacials. To explain this spatial discrepancy, we present grain size and palaeomagnetic analysis of the 202.49‐m long loess drilling core obtained from Ili Basin, documenting environmental history of the past 900 ka, and performed modeling with Community Earth System Model 1.2.2. The sorting coefficient of grain size is used as an indicator for wind intensity in Ili Basin and further Northern Hemisphere ice volume (NHIV). We found an increased NHIV during marine isotope stage 11, 9, and 7 relative to pre‐MBT interglacials, in contrast to variation of Southern Hemisphere ice volume. Supported by numerical modeling experiments, we suggest that asymmetric inter‐hemisphere ice volume could lead to spatial variation in precipitation intensities during interglacials over Asia. Key Points: The thickest loess borehole in the Ili Basin, Central Asia is studied A new record reflecting indirectly Northern Hemisphere ice volume (NHIV) covering the past 900 ka is presented Relatively increased NHIV during marine isotope stage 11 (MIS 11), MIS 9, and MIS 7 caused heterogeneity of interglacial precipitation intensity over Asia